Antioxidant and anti-isomerization effects of sesamol and resveratrol on high oleic acid peanut oil. (April 2020) - Huang, Jinian; Sun, Qiang; Song, Guohui; Qi, Shuning; Chen, Jing; Zhang, Peiyu; Geng, Tingting; Lin, Qiong; Duan, Yuquan
Abstract: In the present study, the protective effects of sesamol and resveratrol on high oleic acid peanut oil were investigated. Different amounts of sesamol, resveratrol, and their combinations were added to the high oleic acid peanut oil to investigate the antioxidant effect and anti-isomerization effect to prevent cis to trans isomerization of double bonds. Rancimat results showed that the oil had the longest oxidation inducing time after adding 0.08% sesamol or 0.06% resveratrol (v/v). Thermogravimetric analysis suggested that when sesamol and resveratrol were added at 0.08% and 0.04% (v/v), the oxidation decomposition temperature was the highest. Schaal oven experiments indicated that the addition of sesamol and resveratrol could significantly reduce the peroxide content of high oleic acid peanut oil. The total fatty acid content in the oil samples increased significantly after high temperature treatment at 180 °C or 240 °C, and three new thermal isomerization trans products were measured (C18:1-9t, C18:2-9c, 12t, C18:2-9t, 12c). Meanwhile, the addition of sesamol (0.08%, v/v) or resveratrol (0.06%, v/v) significantly reduced the content of unsaturated fatty acid. For high oleic acid peanut oil heated to 180 °C, sesamol and resveratrol showed a better inhibitory effect on the production of trans -oleic acid than when heating at 240 °C. Highlights: Protection effects of sesamol and resveratrol on oil were compared. Oil adding 0.08% sesamol showed the best oxidation stability. 0.04%–0.06% resveratrol increased oil antioxidant capacity significantly. Adding sesamol and resveratrol reduced the content of unsaturated fatty acid.